PENINGKATAN EKONOMI MASYARAKAT DESA CURUG KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR MELALUI PELATIHAN PEMBUATAN KERUPUK IKAN LELE - Sri Sulasminingsih; Fahrudin; Luh Desi Puspareni Puspareni; Budhi Martana (Servirisma, 2021)
Community partnership program activities aim to assist the Family Welfare and Empowerment Team (TP-PKK) in implementing community empowerment programs through training activities on making crackers as processed catfish products, and as an effort to realize community economic improvement. The problems faced by partners are (1) there is no effort to utilize the potential of catfish cultivation into food products, (2) there is still a lack of community skills in making catfish processed food products, and (3) processed catfish products have not been maximized as a community business pilot. The method used to achieve the goal is to provide socialization, training and assistance in making catfish crackers. The results obtained from this activity, namely the knowledge and skills of partners increase and are able to create businesses that have an impact on improving the community's economy.